A Wideband mm-Wave Printed Dipole Antenna for 5G Applications - Dewan Atiqur Rahman; Sarah Yasmin Mohamad; Norun Abdul Malek; Dewan Arifur Rahman; Siti Normi Zabri (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this paper, a wideband millimeter-wave (mm-Wave) printed dipole antenna is proposed to be used for fifth generation (5G) communications. The single element antenna exhibits a 36 GHz bandwidth with more than 85.71% fractional bandwidth (for S11 <-10 dB) which covers six of the 5G candidate frequencies; 24 GHz, 25 GHz, 28 GHz, 32 GHz, 38 GHz and 40 GHz. The antenna also exhibits an average gain of 5.34 dB with a compact size of 7.35 x 5.85 mm2. The antenna is further designed to be an array with eight elements and manage to increase the gain of the antenna with an average of 12.63 dB, a fractional bandwidth of 81.48% and linearly-polarized radiation pattern.